Determining The Shortest Path Between Terminal and Airport in Yogyakarta Using Trans Jogja with Min Plus Algorithm - Eka Susilowati; Fenny Fitriani (MUST: Journal of Mathematics Education, Science and Technology, 2019)
Route arrangement is an important factor to be considered so that areas in Yogyakarta city can be reached by Trans Jogja bus. One of the routes to consider is the route that connects between the terminal and the airport in Yogyakarta. Jombor terminal, Giwangan terminal, Condong Catur terminal, and Prambanan terminal are terminals in Yogyakarta. In this paper, we discussed the shortest path between the terminal and Adisucipto Airport with the estimated minimum travel time using Trans Jogja bus. Determination of this route is searched by using min plus algorithm. The shortest trajectory presented is the trajectory between Giwangan and Condong Catur terminal, Condong Catur and Prambanan terminal, and Adisucipto Airport and Jombor terminal. This paper is limited to the passage of Trans Jogja bus stop.